2014
DOI: 10.1186/s12870-014-0286-3
|View full text |Cite
|
Sign up to set email alerts
|

Tomato SR/CAMTA transcription factors SlSR1 and SlSR3L negatively regulate disease resistance response and SlSR1L positively modulates drought stress tolerance

Abstract: BackgroundThe SR/CAMTA proteins represent a small family of transcription activators that play important roles in plant responses to biotic and abiotic stresses. Seven SlSR/CAMTA genes were identified in tomato as tomato counterparts of SR/CAMTA; however, the involvement of SlSRs/CAMTAs in biotic and abiotic stress responses is not clear. In this study, we performed functional analysis of the SlSR/CAMTA family for their possible functions in defense response against pathogens and tolerance to drought stress.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 55 publications
(127 reference statements)
6
42
0
Order By: Relevance
“…Furthermore, the expression of SlSR1L and SlSR2L in tomato seedlings is significantly upregulated by drought stress. However, exogenous ABA does not affect the expression of SlSR1L (Li et al 2014). Thus, it is likely that an unknown mechanism existed in CAMTA-mediated drought stress response in tomato.…”
Section: Drought and Salt Responsesmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the expression of SlSR1L and SlSR2L in tomato seedlings is significantly upregulated by drought stress. However, exogenous ABA does not affect the expression of SlSR1L (Li et al 2014). Thus, it is likely that an unknown mechanism existed in CAMTA-mediated drought stress response in tomato.…”
Section: Drought and Salt Responsesmentioning
confidence: 83%
“…oryzae and the rice blast fungus Magnaporthe grisea (Koo et al 2009). In tomato, CAMTA transcription factors, SlSR1 and SlSR3L, also negatively regulate pathogen resistance responses (Li et al 2014). In summary, CAMTA genes may be good resistance candidates for crop breeding.…”
Section: Biotic Stress Responsesmentioning
confidence: 98%
“…Spores were collected from 10-day-old plates by rinsing the culture with 1% maltose buffer, filtered through bi-layered cheesecloth and adjusted to 2 × 10 5 spores/ml for inoculation (Li et al, 2014a). For gene expression analyses, 4-week-old plants were inoculated by foliar spraying with spore suspension or with same volume of 1% maltose buffer as a mock-inoculation control and leaf samples were collected at different time points after inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that ABA regulates the immunity to B. cinerea in tomato through modulating the cuticle permeability and pectin composition in cell wall or suppressing the SA-mediated signaling pathway or the production of nitric oxide (Audenaert et al, 2002; Asselbergh et al, 2007; Curvers et al, 2010; Sivakumaran et al, 2016). A number of genes encoding receptor-like protein kinase TPK1b, transcriptional factors SHINE3, AIM1, SlDRW1, SlSRN1, SlSR1, and SlSR3L (Abuqamar et al, 2008, 2009; Buxdorf et al, 2014; Li et al, 2014a; Liu et al, 2014a,b), histone H2B monoubiquitination enzymes SlHUB1 and SlHUB2 (Zhang Y. et al, 2015), mitogen-activated protein kinase kinase SlMKK2 and SlMKK4 (Li et al, 2014b), phosphatidylinositol-phospholipase SlPLC2 (Gonorazky et al, 2016), NADPH oxidase SlRbohB (Li X. et al, 2015), 12-oxophytodienoate reductase SlOPR3 (Scalschi et al, 2015) and matrix metalloproteinase Sl3-MMP (Li D. et al, 2015) have been identified to play important roles in tomato immunity against B. cinerea . Enzymes involved in biosynthesis of vitamin B6 and trehalose-6-phosphate as well as concurrent over-activation of cytosolic glutamine synthetase and γ-aminobutyric acid shunt are also involved in tomato immune response to B. cinerea (Seifi et al, 2013; Zhang et al, 2014, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A second possibility is that the divergence of pathways is considerably greater in S. pennellii, and this may lead to a rerouting of carbon into alternate metabolites thereby reducing the pool sizes of the core pathway intermediates. Given that transcriptional control of secondary metabolism has been demonstrated to be quite complex, at least occasionally (for instance, see Li et al, 2014), a third possibility is that primary metabolism is simply under more constrained evolutionary pressures, while secondary metabolism might be under more diversifying selection. While we favor the former two hypotheses, we cannot currently formally exclude any of them.…”
Section: Discussionmentioning
confidence: 99%